Perancangan dan Pengembangan Platform Software-as-a-Service (SaaS) untuk Manajemen Sumber Daya Manusia yang Efisien Pada Health CareRes Apps - Solisisokhi Gee (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
This article discusses the design and development of Health CareRes Apps, a Software-as-a-Service (SaaS) platform designed to efficiently detect skin diseases and support human resource management. The app integrates advanced technologies for image analysis and medical data, providing direct access to healthcare and education. This study explores the advantages of applications, ways of working, operating systems, and medical innovations presented, as well as their implications and benefits for human resource management in organizations.